Pengaruh Paham Liberalisme dan Neoliberalisme Terhadap Pendidikan Islam di Indonesia - M. Yunus Abu Bakar (Universitas Darussalam Gontor, 2012)
This paper is aimed at discussing the influence of liberalism dan neo-liberalism in Islamic Education in Indonesia. The existence of Islamic education is always dealing with and grappling with the reality surrounding them. The struggle between Islamic education to meet socio-cultural reality are two possibilities: a. Islamic education gives impact on socio-cultural environment; b. Islamic education is influenced by the reality of social change, by socio-cultural environment. The ideology of liberalism and neo-liberalism, rationalism, freedom, responsibility, fairness, and tolerance are ideals struggled by liberalism, despite the fact that some ideal values fail to realize. While neoliberalism is actually understood the existence of liberal capitalism is the ideology of liberalism that has led to the economic sector. The influence of not only the political, social, and economic, but in education as well which is a view that emphasizes the development of capabilities, to protect the rights and freedoms as well as identify problems and social change efforts in order to maintain stability for a long time. Central ideas of education revolves around the application of the concept of rationality, freedom, and equality. Education is a democratic distribution of rationality with a balanced treatment, between freedom and equality of rights and obligations, students. Teachers function as facilitators and change the learning process. Philosophycally running constructivism learning including the development of capitalization of education in the form of education commercialization. The fact also has affected in the world of Islamic education.